A CONCEPTUAL APPROACH TO THE CREATION OF AN INFORMATION SUPPORT SYSTEM FOR THE WORKS RELATED TO THE MANAGEMENT OF THE GEOLOGICAL ENVIRONMENT IN THE CONTEXT OF THE LOCALIZATION OF MUNICIPAL SOLID WASTE - AZIMOV, Oleksandr; ROGOZHIN Оleсsij; TROFYMCHUK, Oleksandr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article considers the recent world approaches to municipal solid waste (MSW) management, describes two classes of the objects for their localization such as the unauthorized dumps and disposal landfills which play different functional roles in waste management. Together with the host and surrounding components of the environment the landfills and the dumps are represented as a special environmentaltechno(anthropo)genic system. Since the waste itself is deposited into the geological environment (GE), within the framework of this system in a whole, the technogenic-geological subsystem is considered, which can be represented by certain functional model or an infogeoframe for specified application (i.e. target-oriented). Conceptually, a methodical complex of information support is proposed for the researches and works on the management of GE, where MSW is located. This complex should include two blocks: a prognostic-retrospective-static model for the GE and an integrated ecological-geological model for the technogenic-geological object. Therefore, the main service tool of the information support for the MSW management of the objects of localization in the GE is a provision of the information-functional models for the certain infogeoframes. Completeness of these ecological-geological models is specified by the goals and problems of the management of reference class of the objects (an abstract infogeoframe). An illustration of the filling the information model by some data and its implementation into the Kyiv’s Landfill area No 5 is present. The main directions of further research are outlined.